Diverse transitions in diabetes status during the clinical course of patients with resectable pancreatic cancer. (6th August 2020) - Shingyoji, Ayako; Mikata, Rintaro; Ogasawara, Sadahisa; Kusakabe, Yuko; Yasui, Shin; Sugiyama, Harutoshi; Ohno, Izumi; Kato, Jun; Takano, Shigetsugu; Yoshitomi, Hideyuki; Ohtsuka, Masayuki; Kato, Naoya
Abstract: Objective: Pancreatic cancer and diabetes status have complex bilateral interactions; therefore, understanding their clinical features is essential for the clinical management of pancreatic cancer patients. We aimed to evaluate the diabetes status before diagnosis, after resection and until the time of recurrence in patients with resectable pancreatic cancer and to clarify the correlations among the clinical course of pancreatic cancer, operative procedure and diabetes status. Methods: Between 2011 and 2016, we retrospectively identified 189 pancreatic cancer patients who underwent pancreatoduodenectomy or distal pancreatectomy at our institution. The entire clinical course of each patient was retrieved from the medical records, and the diabetes status in the longest possible duration was assessed. Results: Among 115 pancreatic cancer patients who had normal glucose tolerance at the time of resection, 22 (19.1%) developed type 2 diabetes after resection. In a multivariate analysis, distal pancreatectomy was strongly associated with the development of postoperative diabetes. On the other hand, 74 pancreatic cancer patients had already been diagnosed with type 2 diabetes at the time of resection. During the follow-up period, 15 patients were noted to have diabetes resolution after resection; interestingly, the majority of these patients had newly diagnosed diabetes, which was defined as the diagnosis of diabetes within 3 months before resection. Moreover, newly diagnosed diabetes was an independent factor for diabetes resolution after resection. Conclusions: In pancreatic cancer patients who underwent pancreatectomy, distal pancreatectomy was correlated with postoperative diabetes, and newly diagnosed diabetes had a high probability of resolution after resection. Abstract : We evaluated the diabetes status in patients with resectable pancreatic cancer. Distal pancreatectomy was correlated with postoperative diabetes, and newly diagnosed diabetes had a high probability of resolution after resection.